Cloning and Expression of a Cytosolic HSP90 Gene in Chlorella vulgaris. (13th March 2014) - Liu, Zhengyi; Zhang, Lei; Pu, Yang; Liu, Zhaopu; Li, Zhiling; Zhao, Yushan; Qin, Song
Abstract : Heat shock protein 90 (HSP90), a highly conserved molecular chaperone, plays essential roles in folding, keeping structural integrity, and regulating the subset of cytosolic proteins. We cloned the cDNA of Chlorella vulgaris HSP90 (named CvHSP90) by combining homology cloning with rapid amplification of cDNA ends (RACE). Sequence analysis indicated that CvHSP90 is a cytosolic member of the HSP90 family. Quantitative RT-PCR was applied to determine the expression level of messenger RNA (mRNA) in CvHSP90 under different stress conditions. C. vulgaris was kept in different temperatures (5–45°C) for 1 h. The mRNA expression level of CvHSP90 increased with temperature from 5 to 10°C, went further from 35 to 40°C, and reached the maximum at 40°C. On the other hand, for C. vulgaris kept at 35°C for different durations, the mRNA expression level of CvHSP90 increased gradually and reached the peak at 7 h and then declined progressively. In addition, the expression level of CvHSP90 at 40 or 45 in salinity (‰ ) was almost fourfold of that at 25 in salinity (‰ ) for 2 h. Therefore, CvHSP90 may be a potential biomarker to monitor environment changes.